Weak Institutional Interaction: Reason for Poor Agricultural Extension Services Delivery in Nepal - Devkota, Kamal; Thapa, Dhanej; Dhungana, Hari (New Angle: Nepal Journal of Social Science and Public Policy, 2016)
Institutional pluralism, privatisation and decentralisation of extension services are priority sectors of Nepal’s agricultural extension strategy. With the approach of public private partnership in agriculture, new actors like agro-vet, NGOs, private agro- farm, breeding centres, seed and fertilizer companies have grown considerably in the past decades. This has called a need to outline in detail how institutions communicate and co-operate with each other to forge an effective consolidation for achieving food security, livelihoods and other goals. This paper tries to see current process of agricultural institutional interaction and explore different hurdles in effectively reaching to farmers. With the review of literatures, policy documents and empirical evidences collected from local practitioners and observation of field settings from two districts of Nepal, this paper argues that the existing pattern of institutional interaction for the agricultural intensification is weak. The open political environment and incentive of selling seeds, pesticides and agriculture equipments has resulted into unprecedented rise of agrovets, equipment vendors and dealers—and with time they are becoming more and more influential, having very close links with the farmers. Agriculture extension system remains poorly coordinated among government organisations and NGOs and also has limited communicative links to groups and associations of farmers.